(untitled) (Journal Of Educational and Psychological Researches, 2022)
This study aimed to reveal the extent to which the values of social peace are included in the content of social and national studies textbooks of the middle stage in kingdom of Saudi Arabia. To achieve this goal, the researcher used the descriptive analytical approach. The study sample consisted of all developed social and national studies textbooks of the middle stage in kingdom of Saudi Arabia in first and second semester of student books in edition of 1439-1440. The study tool was the analysis card. The study reached the following results: 1-The content of social and national studies textbooks of the middle stage in kingdom of Saudi Arabia as a whole included (38) social peace values of total (40) values, corresponding to the inclusion rate of (95%), and with the total frequency (769) times. 2- The inclusion of the values of community peace in the content of social and national studies textbooks of the middle stage in kingdom of Saudi Arabia was characterized by imbalance, where emphasis was placed on some values of community peace at the expense of others, foremost among them were the value of "pride of the homeland" and the value of "pride in leadership and national symbols and their roles", with percentage of (33.29%) and (13.52%) respectively, while many other values such as values of" non- spreading rumors, renunciation of racism, do not abusing others (bullying), rejecting terrorism, rejecting discrimination, practicing a culture of volunteerism, promoting social solidarity, and committing to discipline and moderation with low inclusion rates ranging from (0.13%) to (0.52%), in addition, the values of consolidating democracy and fighting corruption are not included at all. 3- There were statistically significant differences at the level of significance (0.05) in inclusion of the values of social peace in the content of social and national studies textbooks of the middle stage in kingdom of Saudi Arabia according to the grade, in favor of the third grade textbooks compared to the textbooks of the first and second grades, respectively. The researcher came out with a number of recommendations and proposals, most notably: the interest of those who develop social and national studies textbooks of the intermediate stage in the Kingdom of Saudi Arabia in advance planning the values of community peace to be included in the content of these books, especially in the first and second intermediate grades textbooks, taking into account the balance, sequence, inclusion and logical order of these values, and the necessity of cooperation of those who develop social and national studies textbooks of the middle stage in Saudi Arabia with the specialists in the field of community peace in the development of the content of these books.